ANALYSIS OF FACTORS RELATED TO JOB SATISFACTION OF NURSES IN THE INPATIENT INSTALLATION AT RSU TANGERANG SELATAN IN 2023 - Susi Lestari; Hardiman SG (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
An indication of effective management is job satisfaction, which is correlated with an individual's sentiments and attitudes regarding the job, pay, possibilities for advancement or education, coworkers, workload, and supervision. According to earlier studies, nurses in RSU Tangerang Selatan’s inpatient installation were influenced by their productive workload by 86.9% to 90.31 percent. Finding the relationship between the variables influencing nurses' job satisfaction in inpatient installations at RSU Tangerang Selatan in 2023 is the aim of this study. A cross-sectional design will be used for this investigation, which will be carried out in April 2023. A total of 59 respondents were used in the sampling process. The chi-square test was used to do the bivariate analysis. 52.5% of nurses believe that the pay structure is bad, 78% believe that training is bad, and 35.6% believe that promotions are bad. The bivariate test results indicated a correlation between pay and promotion (P = 0.014), work satisfaction, and compensation (P = 0.003). training (P = 0.403), indicating that there is no correlation between training and current satisfaction. According to the study, several factors might influence nurses' job satisfaction. Pay and promotions have a strong correlation with job satisfaction, which may raise concerns for the hospital. Hospitals are advised to focus more on the promotion and compensation structure.